The Challenges of the Young Christian and the Religious Freedom in the Postmodern Society (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2017)
The first part of our study presents some of the challenges of the young Christian in the postmodern society and some solutions offered by Church through Christ. We may affirm that the young people are living nowadays a period characterised by changes that challenge the Christian faith and mission. Young people are inclined to choose between fragments of truth, different thinking systems and concept in accordance with their way of seeing reality or in accordance with their own opinions upon spiritual growth. Postmodernity creates a series of difficulties for the young generations: incertitude, doubts, lack of acceptability for different truths about faith and morality, which are not in accordance with their opinion. All these seem to limit the manifestation of freedom. Church is a real defender and preserver of the human values, meaning the sacred value of life, freedom, family and solidarity. The young people need the Church and the Church needs the young people. The second part of the study has freedom and consciousness as themes, always inseparable from the individual. Thus, it is not an error to consider that one of the simplest definitions of a person is freedom itself. We may not speak about any type of freedom – religious, of consciousness and thinking – without reminding Christ, the giver of life and freedom. Where Christ is present, freedom is present. Without Christ, the Supreme Truth, there is no freedom, just the impression of a false freedom.